António Vieira: A Jesuit Missionary to the Portuguese Jews of Amsterdam - Muhana, Adma (Journal of Jesuit studies, 2021)
Abstract Between the years 1646 and 1648, António Vieira maintained close contact with the Portuguese-Jewish community of Amsterdam, in particular with Menasseh ben Israel, a rabbi of Portuguese-converso origin. Under interrogation by the Inquisition, Vieira characterized this period of his life as the one in which he began to elaborate his messianic thesis of the so-called Fifth Empire. Unlike ben Israel, however, Vieira maintained that the Fifth Empire would arrive when the Jews recognized Christ as the messiah. Moreover, commanded by a Portuguese emperor-king, these Fifth Empire Christianized Jews would have their own political state, king, and cultural ceremonies. Always a missionary, Vieira argued that Jews would convert to the Catholic faith without the use of force as long as their idiosyncratic expectations were accepted, much like the Asian peoples and Indians of the New World, who, despite having been converted by the Jesuits, maintained some of their customs, beliefs, and institutions.